2011
DOI: 10.5365/wpsar.2011.2.1.002
|View full text |Cite
|
Sign up to set email alerts
|

Male-female differences in the number of reported incident dengue fever cases in six Asian countries

Abstract: These data indicated the importance of reporting data stratified by both sex and age since collapsing the data over all ages would have masked some of the male-female differences. To target preventive measures appropriately, assessment of gender by age is important for dengue because biological or gender-related factors can change over the human lifespan and gender-related factors may differ across countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
100
7
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 13 publications
37
100
7
2
Order By: Relevance
“…The male predominance has also been reported in several other studies [6]. The mean age of patients in our study was 32.4 years which is similar to other studies where higher age groups were observed of developing symptomatic disease than younger groups [7][8][9] and contradictory to the study by Raut and Patil where they revealed children <10 years were affected more [10].…”
Section: Discussionsupporting
confidence: 86%
“…The male predominance has also been reported in several other studies [6]. The mean age of patients in our study was 32.4 years which is similar to other studies where higher age groups were observed of developing symptomatic disease than younger groups [7][8][9] and contradictory to the study by Raut and Patil where they revealed children <10 years were affected more [10].…”
Section: Discussionsupporting
confidence: 86%
“…7 In the present study, male predominance (62%) was noted which is in comparable with the previous study conducted in six asian countries by anker et al In addition, our study also showed that the bleeding tendencies are common in females (57%) as compared to males. 8 In our study we also found that fever (92%) and vomiting (44%) are the most common presenting illness. Among all bleeding manifestations, melena (48%), petechial hemorrhages (28%) are common .…”
Section: Bleeding Signs Discussionsupporting
confidence: 67%
“…[5] Three independent studies from epidemics in India done by Agarwal et al, Ray et al, and Wali et al, also found nearly twice the number of male patients infected with dengue compared to females, M:F being 1.9:1, 1:0.57, and 2.5:1, respectively.…”
Section: Discussionmentioning
confidence: 92%